2012
DOI: 10.1134/s1063783412070220
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculations of neutral and charged impurity centers of manganese and chromium in strontium titanate

Abstract: This paper presents the results of ab initio calculations of the equilibrium geometry, the electronic structure, and the spin and charge densities for neutral and negatively charged defects produced by the Mn and Cr impurities in the B position of the SrTiO 3 structure. It has been shown that, in both cases, the neutral defect is an acceptor center, while the singly charged defect is a donor center. It has been found that doubly charged defects are polar, have the symmetry C 4v , and reside in the ionic config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This latter property is closely related to doping with transition metal impurities, such as chromium, as well as to thermal treatments and ion irradiation that introduce oxygen vacancies. In particular, chromium doping appears to play a key role in all these processes and allows for a reversible insulator-to-conductor transition or resistive memory effect . It is generally accepted that the Cr dopant ions in STO substitute for Ti 4+ and occupy an octahedral site as Cr 4+ but shift to Cr 3+ under electronic excitation. The possibility of other valence states, such as Cr 6+ , as well as the occupancy of Sr sites has been also discussed, mostly in connection with the photocatalytic response of STO, since this activity is very dependent on the charge state of chromium. One should remark that the charge state is strongly influenced by the location of the Fermi level in the STO crystal, which can be modified through impurity doping, thermochemical treatments, and irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…This latter property is closely related to doping with transition metal impurities, such as chromium, as well as to thermal treatments and ion irradiation that introduce oxygen vacancies. In particular, chromium doping appears to play a key role in all these processes and allows for a reversible insulator-to-conductor transition or resistive memory effect . It is generally accepted that the Cr dopant ions in STO substitute for Ti 4+ and occupy an octahedral site as Cr 4+ but shift to Cr 3+ under electronic excitation. The possibility of other valence states, such as Cr 6+ , as well as the occupancy of Sr sites has been also discussed, mostly in connection with the photocatalytic response of STO, since this activity is very dependent on the charge state of chromium. One should remark that the charge state is strongly influenced by the location of the Fermi level in the STO crystal, which can be modified through impurity doping, thermochemical treatments, and irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Kvyatkovskii investigated the geometry and electronic structure for defects produced by the Mn impurities both in SrTiO 3 and KTaO 3 . 28, 29 He used a cluster approach where the crystalline environment of the defect is modeled by a cluster that is passivated by hydrogen atoms. Kondakova et al in their local spin density approximation (LSDA) calculations showed that a Mn ion substituting for Sr in SrTiO 3 occupies the off-central position.…”
mentioning
confidence: 99%